Designing Artificial Fluorescent Proteins: Squaraine‐LmrR Biophosphors for High Performance Deep‐Red Biohybrid Light‐Emitting Diodes. (17th January 2022) - Ferrara, Sara; Mejias, Sara H.; Liutkus, Mantas; Renno, Giacomo; Stella, Francesca; Kociolek, Irene; Fuenzalida‐Werner, Juan Pablo; Barolo, Claudia; Coto, Pedro B.; Cortajarena, Aitziber L.; Costa, Rubén D.
Abstract: Biophosphors with fluorescent proteins (FPs) are promising candidates to replace rare‐earth color down‐converting filters for white light‐emitting diodes (LEDs). There is, however, a lack of deep‐red FPs meeting high photostabilities, photoluminescence quantum yields (ϕ), and throughput expression yields. Herein, a new approach for the design of highly emissive and stable deep‐red biophosphors combining an artificial FP (Lactococcal multidrug resistance Regulator (LmrR) as protein host and an archetypal red‐emitting squaraine (S) as guest) with a polymer network is demonstrated toward high performing deep‐red biohybrid LEDs (Bio‐HLEDs). At first, the best protein pocket (aromaticity, polarity, charge, etc.) to stabilize S in water is determined using four LmrR variants (position 96 with tryptophan, histidine, phenylalanine, and alanine). Computational and time‐resolved spectroscopic findings suggest that the tryptophan is instrumental toward achieving artificial red‐emitting FPs with ϕ > 50% stable over weeks. These features are further enhanced in the polymer coating (ϕ > 65% stable over months) without affecting emission color. Finally, deep‐red Bio‐HLEDs are fabricated featuring external quantum efficiencies of 7% and stabilities of ≈800 h. This represents threefold enhancement compared to reference devices with S‐polymer color filters. Overall, this work highlights a new design for highly emissive deep‐red biophosphors, achieving record performance in deep‐red protein‐LEDs. Abstract : Design of deep‐red biophosphors with artificial fluorescent proteins combining Lactococcal multidrug resistance Regulator (host) and a highly emissive squaraine (guest), realizing deep‐red Bio‐HLEDs with external quantum efficiencies of 7% and month stabilities.